DOI: 10.31274/rtd-180813-9591
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for computerized adaptive testing: golden section search, dichotomous search, and Z-score strategies

Abstract: Item pools and item selection methods Results Comparison of two item selection methods Comparison of two versions of ZSS .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The finalθ is the MLE. Z-score strategies have also been shown to be very effective for a broad range of CATs (Xiao, 1993). ZGT was adapted from the Z-score strategies for CAT.…”
Section: Z-score Search Cat and Zgtmentioning
confidence: 99%
See 2 more Smart Citations
“…The finalθ is the MLE. Z-score strategies have also been shown to be very effective for a broad range of CATs (Xiao, 1993). ZGT was adapted from the Z-score strategies for CAT.…”
Section: Z-score Search Cat and Zgtmentioning
confidence: 99%
“…The obtained score, x, was compared to the expected score at the midpoint of the search region. If x was greater or less than, respectively, the upper or lower bound of the confidence interval of the expected score µ x|θ ± .7σ x|θ , that side of the search region was discarded [.7 is an arbitrary weight used in the present study, based on Xiao (1993) who showed that GSS strategies were most efficient at .7]. The size of successive golden search regions was reduced by a ratio t (see Equation 1).…”
Section: Testsmentioning
confidence: 99%
See 1 more Smart Citation